Social media influence on Eating Disorders since COVID-19 pandemic: a pilot study - F. Micanti; G. Spennato; R. Claudio; E. Amoroso; M. D’Ambrosio; V. M. Saia; A. Barone; M. Tadic; D. Galletta; M. Vannini (European Psychiatry, 2023)
Introduction Several studies show a negative impact of mass media contents on adolescents’ mental health, especially on perceived body uneasiness. COVID-19 lockdown determined an increased use of social networks (SN). Psychiatrists highlighted an increase in Eating Disorders’ (ED) diagnoses. Objectives The aim of this study is to assess the pattern of SN use in patients with ED using a self-administered questionnaire. Methods 30 patients with clinical diagnosis of ED (Anorexia nervosa, Bulimia nervosa or Binge eating disorder) admitted to the ED unit, underwent clinical assessment, and filed a questionnaire on SN use. The questionnaire assesses time spent on SN, weight-control apps use, exposure to fitness- or food-related contents and to ED-promoting contents, distractibility, weight changes and feeling of body uneasiness. Results Mean age was 20.63 (SD 4.71), mean BMI 20.24 (SD 5.27); 93.3% (28) of patients were females. Eating behaviours were divided into restrictive type (66.7%, 20) or binge/bulimic (33.3%, 10). 16.7% (5) of patients reported self-injury behaviours. In 46.7% (14) of cases, the onset of the ED occurred during COVID-19 pandemic; the remaining 53.3% (16) experienced a relapse of a previous ED during this period. 66.7% (20) of subjects reported an increased use of social media and fitness apps. 90% (27) experienced weight changes during the pandemic, with 76.7% (23) seeking nutritional or psychological interventions. 53.3% (16) perceived an increase in body- or food-related contents on their SN feeds, with 50% declaring of knowing the meaning of the terms pro-ana and pro-mia.